An Analysis of Verbal Interaction Between Teacher and Students in the Classroom at Eight Grade of State Junior High School 3 Tambusai Utara - Muhammad Taufik Ihsan (Nalar Global, 2023)
This research aimed to know the verbal interaction between teacher and students and the dominant of verbal interaction that occur in the learning process at Eight grade State Junior High School 3 Tambusai Utara. This research used qualitative research. The method used in this research was descriptive qualitative. This research was held at State Junior High School 3 Tambusai Utara. The techniques of data collection used were observation and interview. The participants of this research were an English teacher and 14 students. The technique of sample selection in this research was purposive sampling. The techniques of data collection used were observation and interview. After getting the data, the researcher used the model of Miles and Huberman, they are data collection, data reduction, data display, and drawing conclusion. The results of this research found, from 7 categories of verbal interaction in teacher talk by FIACS the researcher found 6 categories that occur during learning process, such as accept feeling, praise or encourages, asking question, lecturing, giving direction and criticizing or justifying the authority. Only accept to use student’s idea that do not occurred during learning process because the students did not deliver their idea in the learning process. Meanwhile in the students talk by FIACS, from 3 categories only 2 categories that occur, they are students[1]talk response and silence. There is not found students-talk initiation in the classroom. Then, the researcher found that the teacher more active than the students in the verbal interaction during learning process. The students talked a lot when they gave responses to the teacher’s question. It means, the teacher’s talk more dominant than student’s talk.